Brain Network Constancy and Participant Recognition: an Integrated Approach to Big Data and Complex Network Analysis - Qiu, Lu; Nan, Wenya (Frontiers in Psychology, 2020)
With the development of big data sharing and data standardization, electroencephalogram (EEG) data are increasingly used in the exploration of human cognitive behavior. Most of the existing studies focus on the changes of human brain network topology (the number of connections, degree distribution, clustering coefficient phantom.) in various cognitive behaviors. However, there has been little exploration into the steady state of multi-cognitive behaviors and the recognition of multi-participant brain networks. To solve these two problems, we used EEG data of 99 healthy participants from the PhysioBank to study the multi-cognitive behaviors. Specifically, we calculated the symbolic transfer entropy (STE) between 64 electrode sequences of EEG data and constructed the brain networks of various cognitive behaviors of each participant using the directed minimum spanning tree (DMST) algorithm. Then we investigated the eigenvalue spectrum of the STE matrix of each individual's cognitive behavior. The results also showed that the spectrum distributions of different cognitive states of the same participant remained relatively stable, but those of the same cognitive state of different participants varied considerably verifying the relative stability and uniqueness of the human brain network which is similar to human's fingerprint. Based on these features, we used the spectral distribution set of 99 participants of various cognitive states as the original data set, and developed a spectral distribution set scoring(SDSS) method to identify the brain network participants. It was found that most labels 69.35% of the test participant with the highest score were identical with the labeled participant. This study provided further evidence for the existence of human brain fingerprints, and furnished a new approach for dynamic identification of brain fingerprints.